A Novel System for Estimating Residual Disease and Pathologic Response to Neoadjuvant Treatment of Prostate Cancer. Issue 14 (8th June 2016) - Murphy, Claire; True, Lawrence; Vakar‐Lopez, Funda; Xia, Jing; Gulati, Roman; Montgomery, Bruce; Tretiakova, Maria
Abstract : BACKGROUND: Pathologic variables that characterize response of prostate carcinoma to current neoadjuvant therapy have not been characterized in detail. This study reports (i) the histological features of prostate cancer treated with abiraterone and enzalutamide and inter‐pathologist variance in identifying these features, and (ii) the effect of the novel androgen deprivation agents on residual cancer volume. METHODS: We reviewed sections of prostatectomies from 37 patients treated with neoadjuvant agents and 22 untreated patients, tabulated the frequency of nine features of cancer (intact cancer glands, isolated cancer cells, poorly formed glands, cribriform architecture, clear spaces, intraductal carcinoma, solid sheets of cancer cells, prominent nucleoli, and previously described ABC grouping) and two features of benign glands (prominent basal cells and coalescent corpora amylacea). We used several methods, including a novel metric (visual grid system), to estimate residual tumor volume. RESULTS: The most highly reproducible features were ABC grouping (κ = 0.56–0.7), presence of intraductal carcinoma (κ = 0.34–0.72), cribriform architecture (κ = 0.42–0.68), solid sheets of tumor cells (κ = 0.44–0.56), and coalescent corpora amylacea (κ = 0.4–0.54). Among poorly reproducible features were prominent nucleoli (κ = 0.03–0.11), clear spaces (κ = 0.05–0.07), and poorly formed cancer glands (κ = 0.02–0.1). Determination of tumor mass was excellent regardless of the method used—maximum tumor size (κ = 0.9–0.94), tumor area (κ = 0.94–0.96), and grid‐based tumor cellularity (κ = 0.9). CONCLUSIONS: We propose using a set of parameters including maximum tumor size, tumor area/volume, cellularity, volume, and ABC grouping for evaluating radical prostatectomies post‐neoadjuvant therapy. Prostate 76:1285–1292, 2016 . © 2016 Wiley Periodicals, Inc.